Recovery of peptide from Nannochloropsis gaditana protein hydrolysate through two-stage ultrafiltration membrane - Md Saleh, Nur Izzati (2021)
Microalgae Nannochloropsis gaditana (N.gaditana) is widely recognized as potential source of biofuel due to its high lipid content. However due to high cost of production, microalgae biorefinery concept was approached. Microalgae‘s protein which consists up to 50% w/v has a value added. Peptides derived from microalgae‘s protein offers great potential value for food and pharmaceutical products. In this study, enzymatic hydrolysis of N.gaditana using alcalase was optimized using Response surface Methodology (RSM) with different variables; pH, temperature, enzyme concentration and substrate concentration. Optimum conditions were obtained at pH 8.14, temperature 51.4°C, 5.48 g/L substrate concentration and 0.26 g/L enzyme concentration with predicted degree hydrolysis of 55.76%. Microalgae protein hydrolysate (MPH) had 17.9% of total lipid, 55.73 % of total protein, 6.8% of total carbohydrate, 15.42% of ash and 4.15% of moisture with high total amino acid of 2507.297 mg/100g which indicated the high nutritional value in MPH as a potential source of functional food. Since MPH was composed of peptides with different molecular weight, fractionation using ultrafiltration (UF) membrane was conducted with two different membrane configurations; single (10 kDa and 5 kDa) and two-stage (10/5 kDa) to obtain peptide with low molecular weight that could improve the biological activity of N.gaditana. Three different parameters (pH, feed flow rate and trans-membrane pressure) were evaluated based on permeate flux and peptide transmission. The best fractionation of MPH was observed using two-stage 10/5 kDa UF membrane at flow rate of 23 ml/min, 1.5 Bar of trans-membrane pressure and pH 2 with permeate flux of 69.85±1.22 L/m2h and peptide transmission of 79.13±0.50%. High peptide recovery were found using two-stage UF membrane with 58.04%, followed by 10 kDa and 5 kDa UF membrane with 15.70% and 7.26%, respectively. Peptide from two-stage 10/5 kDa UF membrane were mainly consists of peptide with molecular weight below 300 Da with 77.49%. Peptide sequence from fractionated MPH using two-stage 10/5 kDa UF membrane was identified as Leu-Leu-His-Ala-Leu-Leu. The presence of small peptide size, hydrophobic amino acids and histidine were contributed to high antioxidant activity of the peptide. In summary, MPH fractionation using two-stage 10/5 kDa UF membrane were observed could enrich low molecular weight of peptide and enhance antioxidant activity.